Analysis of waste management issues arising from a field study evaluating decontamination of a biological agent from a building. (2nd January 2016) - Lemieux, P.; Wood, J.; Drake, J.; Minamyer, S.; Silvestri, E.; Yund, C.; Nichols, T.; Ierardi, M.; Amidan, B.
ABSTRACT: The Bio-response Operational Testing and Evaluation (BOTE) Project was a cross-government effort designed to operationally test and evaluate a response to a biological incident (release of Bacillus anthracis [Ba] spores, the causative agent for anthrax) from initial public health and law enforcement response through environmental remediation. The BOTE Project was designed to address site remediation after the release of a Ba simulant, Bacillus atrophaeus spp. globigii (Bg), within a facility, drawing upon recent advances in the biological sampling and decontamination areas. A key component of response to a biological contamination incident is the proper management of wastes and residues, which is woven throughout all response activities. Waste is generated throughout the response and includes items like sampling media packaging materials, discarded personal protective equipment, items removed from the facility either prior to or following decontamination, aqueous waste streams, and materials generated through the application of decontamination technologies. The amount of residual contaminating agent will impact the available disposal pathways and waste management costs. Waste management is an integral part of the decontamination process and should be included through "Pre-Incident" response planning. Overall, the pH-adjusted bleach decontamination process generated the most waste from the decontamination efforts, and fumigation with chlorine dioxide generated the least waste. A majority of the solid waste generated during pH-adjusted bleach decontamination was the nonporous surfaces that were removed, bagged, decontaminated ex situ, and treated as waste. The waste during the two fumigation rounds of the BOTE Project was associated mainly with sampling activities. Waste management activities may represent a significant contribution to the overall cost of the response/recovery operation. This paper addresses the waste management activities for the BOTE field test. Implications: Management of waste is a critical element of activities dealing with remediation of buildings and outdoor areas following a biological contamination incident. Waste management must be integrated into the overall remediation process, along with sampling, decontamination, resource management, and other important response elements, rather than being a stand-alone activity. The results presented in this paper will provide decision makers and emergency planners at the federal/state/tribal/local level information that can be used to integrate waste management into an overall systems approach to planning and response activities.